Reconceptualization of Proximal Nail Fold Reconstruction: Skin Grafting over the Nail Plate - Runa Hara, MD; Daisuke Matsumoto, MD, PhD; Hitomi Funabashi, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. The structure of the periungual area is complicated, resulting in historically difficult morphological reconstruction after trauma or cancer resection. There is also no established standard for its reconstruction; thus, we aimed to use a full-thickness skin graft (FTSG) over the nail plate. Three patients with Bowen disease on their proximal nail fold (PNF) underwent excision with a 2-mm margin preserving the nail matrix, and a temporary wound dressing was applied. The FTSG was harvested from the ipsilateral ulnar wrist joint and placed over the skin defect, including the nail plate. Initially, the FTSG seemed to have shrunken; however, after 3 months, it extended and the PNF had a good color and texture match. Remarkably, the FTSG adhered to the nail plate, and the complex PNF structure appeared well reconstructed. Occasionally, a local flap is used; however, it is limited to small defects and causes a deformity of the periungual structure. In this study, the reconstructed PNF showed good results. We presumed that the bridging phenomenon caused graft survival on the nail plate, and that the presence of stem cells near the nail matrix caused graft extension and eponychium and cuticle regeneration. Specifically, the acquisition of sufficient raw surface around the nail plate and wound preparation after excision resulted in the former, and the nail matrix preservation after excision contributed to the latter. This surgical technique is simple and can therefore be considered a remarkably effective method for periungual area reconstruction to date.